2015
DOI: 10.1093/jxb/erv475
|View full text |Cite
|
Sign up to set email alerts
|

Soybean fruit development and set at the node level under combined photoperiod and radiation conditions

Abstract: HighlightLong days during post-flowering postpone elongation and active growth of dominant pods within a node, which extends flowering and allows pod set at usually dominated positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 55 publications
(91 reference statements)
0
25
0
Order By: Relevance
“…Two hypotheses can be constructed about this phenomenon. The first is that plants with lower EDAS values have greater flowering and fruiting periods by altering intra-nodal pod interactions, similar to the effects that occur when the photoperiod increases, generating more pods [33]. Another hypothesis is that the greater accumulation of photoassimilates leads to greater fruiting [34].…”
Section: Discussionmentioning
confidence: 97%
“…Two hypotheses can be constructed about this phenomenon. The first is that plants with lower EDAS values have greater flowering and fruiting periods by altering intra-nodal pod interactions, similar to the effects that occur when the photoperiod increases, generating more pods [33]. Another hypothesis is that the greater accumulation of photoassimilates leads to greater fruiting [34].…”
Section: Discussionmentioning
confidence: 97%
“…Pod number per node also increased with the duration of the R1 to R3 period in all combinations except June + NIL‐ e4 (Figure S4). Nico, Mantese, Miralles, and Kantolic () reported that artificial photoperiod extension increased pods per node on the main stems, by increasing pods and flowers on lateral racemes and extending the flowering period. Therefore, another possible explanation for the difference in the temperature response of pod number at the node level was the indirect effect such as the phenological change caused by temperature, sowing date (photoperiod), and E4/e4 alleles in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high temperature is reported to delay the onset of seed growth and reduce seed growth rate [19], which may also alleviate the competition. Similarly, it has been reported that the effective seed fillings on primary racemes were delayed by long days, resulting in the prolonged flowering duration and increased number of flowers on lateral racemes [20].…”
Section: Late Opened Flowersmentioning
confidence: 77%